New Trends in Teaching and Learning Theory Dr. Jasim Muhammad Abdul- Slamy (Journal of the College of Education for Women, 2019)
New trends in teaching and learning theory are considered a theoretical axisfrom which came the background that depends on any source, or practice sample orteaching plane, accuracy and simplicity prevent the development of the teachingprocess. Many attempts have come to scene to illuminate the teaching background,but they have not exceed those remarkable patterns and methods. Thus, theappearance of the teaching theory have been hindered.This led to the need for research and development in the field of teaching tofind out a specific teaching theory according to the modern trends and concepts.Teaching is regarded a humanitarian process which aims at helping those whowant to acquire knowledge, since teaching is an intended activity. Education is theprocess of acquiring knowledge, skills and trends by the person who wants to learnhimself / herself. Accordingly, learning is a principal branch of teaching, because it isconsidered one of the varied methods in carrying out the teaching process. From thisfact did the need to use a good theory as a guide to the later researches come. Its valuedepends highly on the studies and researches it produces to help the researcher find away that direct him to discover new aspects.* The Research purpose:This research aims at knowing the new trends and methods in the theory ofteaching and learning.* The Research Boundary:This research is limited to: finding out the theory of teaching and learning andputting a balance between them. In addition to discovering the features and methodsof building the teaching theory. Moreover, it aims at putting a limit to the role playedby the theory in the teaching and learning process.Specifying terminology:Terms concerning teaching and learning are specified in the research itself.